Crimean-Congo haemorrhagic fever among healthcare workers in Iran 2000–2023, a report of National Reference Laboratory - Mehdi Fazlalipour; Tahmineh Jalali; Roger Hewson; Mohammad Hassan Pouriayevali; Mostafa Salehi-Vaziri (BMC Infectious Diseases)
Abstract Background Crimean-Congo haemorrhagic fever (CCHF) is a lethal acute viral zoonosis with a case fatality rate of 5–50%. Due to the potential of human-to human transmission of the disease, healthcare workers (HCWs) are at risk of occupational exposure to CCHF virus. Little is known about CCHF virus route of transmission and risks in Iranian HCWs. Therefore this study was designed to identify the routes of exposure to the CCHF virus among Iranian HCWs. Methods From Oct 2000 to Feb 2023, 96 CCHF suspected healthcare workers referred to national reference laboratory were tested for CCHF virus infection by the use of RT-PCR and IgM Capture Enzyme-Linked Immunosorbent Assay (MAC-ELISA) and exposure history of cases were investigated to determine the CCHF virus routes of transmission in nosocomial settings. Results Twelve CCHF confirmed cases were identified including seven nurses and five physicians, with the median age of 32.5 years (range 23–53 years) and the median incubation period of 6.8 days (range from 1 to 22 days). None of the cases reported a history of tick bite or close contact with tissues or animal blood. The cases were from Razavi Khorasan (seven cases), Sistan and Baluchistan (two cases), Isfahan (one case), South Khorasan (one case) and Fars (one case). Percutaneous exposure (needle stick) (three cases), mucosal exposure (blood splash in to face) (three cases) and skin contact with blood (three cases) constituted the most prevalent routes of transmission. Since 2013, no CCHF cases have been identified among Iranian HCWs. Conclusions In healthcare settings, physicians and nurses are at risk of nosocomial CCHF virus infection. The routes of transmission mainly include direct exposures via needle-stick, mucosal or direct contact with the skin to infected blood. Continuous education and implementation of infection prevention and control measures are key factors to minimize the incidence of healthcare related CCHF.